Predicting the fluid temperature at the exit of the vertical ground heat exchangers - Michopoulos, Apostolos; Kyriakis, N. A. (My University, 2009)
The energy analysis of ground source heat pump systems is based on the instantaneous fluid temperature at the ground heat exchanger outlet. This temperature defines the ground source heat pump coefficient of performance (COP) and hence the electricity consumption required in order to fulfill the energy demands of the building. The aim of this work is to present a model able to predict the fluid temperature at the ground heat exchanger outlet, taking into account the heat transfer phenomena in the soil and the temporal variation of the thermal load of the ground heat exchanger. The model developed was verified using experimental data, expanding over a three years period, of a vertical ground heat exchanger. It is proved that the model is able to satisfactorily predict the recorded temperature values throughout the verification period. The differences between measured and estimated outlet water temperatures impose a deviation between the estimated and the actually recorded electricity consumption of less than 4%.
Keywords: Ground heat exchanger; Ground heat exchanger simulation; COP prediction